Particle-dominated double emulsions: concept of Pickering stabilization, interfacial challenges, and emerging opportunities in food systems - Anuj Niroula; Akmal Nazir; Karin Schroën (Future Foods)
This review aims to highlight the significance of double emulsion (DE) and the promising scope of Pickering stabilization and discuss the underlying challenges and potential opportunities in food systems. DE offers a compartmentalized structure for encapsulating and delivering the hydrophilic and lipophilic active components; however, the inherent instability has hindered their practical application. Introducing particles to the interface has proven revolutionary, significantly improving stability by preventing coalescence and Ostwald ripening. This increased stability is attributed to the high desorption energy of particles, which are orders of magnitude higher than that of conventional emulsifiers. The term “Pickering” refers to interfaces that are stabilized solely by particles. However, Pickering stabilization in most real-world systems like foods is challenging as they are multi-component systems with several other molecules that (even in trace amounts) can adsorb at the interface during or after emulsification. This violates the strict definition of Pickering stabilization and may be stated as “particle-dominated” or “mixed interfaces”. Yet the properties of such DEs can be dominated by particles, offering several innovative applications in food and related disciplines, especially for the encapsulation, targeted delivery, and controlled release of active components or for preparing templated structures like microspheres and antibubbles.